Tafsir Ayat-Ayat Neurosains: Telaah Konsep Ulul Albab Dalam Al-Qur’an - Arsyad, M (Aktualita: Jurnal Penelitian Sosial Keagamaan, 2024)
Human beings are the perfect creation of Allah SWT, with perfection residing in their intellect. In addition to their intellect, humans also possess a brain as the central control for all human activities. This article aims to discuss the concept of Ulul Albab from the perspective of Neuroscience. The term Ulul Albab is found 16 times in the Quran, signifying 'people of intellect,' while Neuroscience is the science that studies the human brain. In the Neuroscience literature review, a focus is placed on the prefrontal cortex. The research type and approach in this study take the form of a literature review. A literature review is an approach used to gather information or sources related to the topic of a study. In this research, the investigator seeks data from journals, articles, or relevant books regarding Neuroscientific-based learning in the Quran.